Weed Control in Strawberry - William M. Stall (EDIS)
Revised! HS196, a 2-page fact sheet by William M. Stall, describes effective weed management practices for strawberries in Florida and provides a table listing herbicides available to growers for chemical weed control. This publication updates the 2003 table to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.